Design of Logistic Transporter Robot System - Lora Khaula Amifia; Mochammad Iskandar Riansyah; Putu Duta Putra (Universitas Ahmad Dahlan, 2020)
The diversity of technology in the robotics world is currently developing a lot, especially in logistics distribution. The distribution of logistics goods using robotic power continues to develop towards high artificial intelligence, ensuring warehouse delivery management and intelligence implementation with challenging tasks. Autonomous robots are a community of intelligent robotic systems that can be seen as prototypes. It is an intelligent management and service system of the future that can reveal some important traits of the next generation of smart robot communities. In the smart logistics industry, designing an efficient communication and management platform from logistics robots is one of the fundamental problems. This study aims to implement smart robots in assisting distribution / logistical activities by following humans in bringing goods to the intended area by following green objects.